Information Easiness Affects Non-experts’ Evaluation of Scientific Claims About Which They Hold Prior Beliefs - Scharrer, Lisa; Bromme, Rainer; Stadtler, Marc (Frontiers in Psychology, 2021)
Usually, non-experts do not possess sufficient deep-level knowledge to make fully informed evaluations of scientific claims. Instead, they depend on pertinent experts for support. However, previous research has shown that the easiness by which textual information on a scientific issue can be understood seduces non-experts into overlooking their evaluative limitations. The present study examined whether text easiness affects non-experts’ evaluation of scientific claims even if they possess prior beliefs about the accuracy of these claims. Undergraduates who strongly believed that climate change is anthropogenic read argumentative texts that were either easy or difficult to understand and that supported a claim either consistent or inconsistent with their beliefs. Results are consistent with the hypothesis that text easiness affects non-experts’ judgement of scientific claims about which they hold prior beliefs – but only when these claims are in accordance with their beliefs. It seems that both text difficulty and belief inconsistency remind non-experts of their own limitations.